2017
DOI: 10.1007/s11102-017-0815-9
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes after endoscopic endonasal pituitary adenoma resection: a systematic review and meta-analysis

Abstract: PurposePatients with pituitary adenomas often present with visual deficits. While the aim of endoscopic endonasal transsphenoidal surgery (EETS) is to improve these deficits, permanent worsening is a possible outcome. The aim of this meta-analysis was to evaluate the effect of EETS for pituitary adenomas on visual outcomes.MethodsA meta-analysis was conducted according to the PRISMA guidelines. Pooled prevalence was calculated for complete recovery, improvement, and deterioration of visual field deficits, visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
52
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 56 publications
6
52
0
10
Order By: Relevance
“…In another study performed by Shigetoshi Yano et al 12 of 74 cases, total gross removal was achieved in pituitary adenomas and in 68% of meningiomas. 13 Macro-adenoma was noted in 67% of cases in our study, which is comparable to studies in which 70% of their cases were macroadenomas. 11,12 Visual function improvement was achieved in 82% of patients in this study, and this improvement was nearly the same as in other studies in which 90% of cases showed visual improvement after surgery.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…In another study performed by Shigetoshi Yano et al 12 of 74 cases, total gross removal was achieved in pituitary adenomas and in 68% of meningiomas. 13 Macro-adenoma was noted in 67% of cases in our study, which is comparable to studies in which 70% of their cases were macroadenomas. 11,12 Visual function improvement was achieved in 82% of patients in this study, and this improvement was nearly the same as in other studies in which 90% of cases showed visual improvement after surgery.…”
supporting
confidence: 85%
“…11,12 Visual function improvement was achieved in 82% of patients in this study, and this improvement was nearly the same as in other studies in which 90% of cases showed visual improvement after surgery. 12,13 In both studies, the majority of cases that developed better visual results complained of pituitary macroadenomas.…”
mentioning
confidence: 95%
“…A recent meta‐analysis evaluating visual outcome in endoscopic transsphenoidal surgery by Muskens et al . found that pooled rate of VA improvement was 67.5% and pooled rate of VF deficit improvement was 80.8%.…”
Section: Intradural Tumorsmentioning
confidence: 99%
“…Postoperative VF deterioration after transsphenoidal surgery occurs in up to 4% of cases . The mechanism can be either direct surgical damage, vascular compromise, postoperative bleeding, overpacking in sealing a CSF leak, or as a consequence of optic nerve and chiasm prolapse into an empty sella .…”
Section: Intradural Tumorsmentioning
confidence: 99%
“…Timely intervention can result in improvement in vision within hours of waking from trans-sphenoidal surgery such that patients are able to read and drive where previously limited. A meta-analysis of visual outcomes after pituitary surgery found that complete recovery was probably less likely if the pre-operative visual defect was severe and of longer duration,14 with one study finding worse outcomes if the visual field deficit had been present for more than a year 15. Visual field defects caused by a macroprolactinoma can also improve rapidly with dopamine agonist therapy 1617…”
Section: Why Does It Matter?mentioning
confidence: 99%